A performance‐emission tradeoff study of a CI engine fueled by compressed natural gas (CNG)/diesel–ethanol‐PPME blend combination. Issue 2 (18th August 2015) - Paul, Abhishek; Panua, Rajsekhar; Debroy, Durbadal; Kumar Bose, Probir
Abstract : In the present study, a blend of 45% diesel, 15% ethanol and 40% Pongamia pinata methyl ester (PPME) has been used as pilot fuel for CNG dual fuel operation in a single cylinder CI engine along with CNG as the primary fuel. The intake manifold of an existing engine is slightly modified for indirect injection of CNG into the engine cylinder. The results are compared with the pilot diesel operation with same CNG injection strategies. It is found that the pilot operation of the blend is instrumental in increasing the brake thermal efficiency of the engine at all the tested load conditions with higher pilot fuel consumption. Pilot operation of the blend also simultaneously reduced NOx, hydrocarbon and CO emissions as compared with pilot diesel operation. Hence, it is found that the pilot blend with 15% ethanol and 40% PPME is useful in improving the performance of the engine with significant reduction in emission with respect to CNG‐diesel duel fuel operation. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 517–530, 2016